Effectiveness of body image directed interventions in patients with anorexia nervosa: A systematic review. Issue 10 (6th September 2018) - Ziser, Katrin; Mölbert, Simone Claire; Stuber, Felicitas; Giel, Katrin Elisabeth; Zipfel, Stephan; Junne, Florian
Abstract : Objective: Body image (BI) disturbances are one of the core symptoms of anorexia nervosa (AN). They have been shown to be associated with depression and anxiety at all treatment stages and are a reliable predictor of relapse. Considering the importance for the course of AN, direct targeting of BI disturbances is still underemphasized in the treatment of patients with AN. Method: In this systematic review, conducted according to the PRISMA statement, the evidence on BI directed interventions in AN is synthesized. Results: N  = 11 studies investigating mirror exposure, video confrontation, virtual reality body exposure and treatment programs were analyzed. No systematic risk of bias within or across studies could be identified. The included studies show that BI directed interventions may be efficacious in improving BI related outcomes. However, the evidence regarding an additional effect of BI interventions added to established treatments for patients with AN, is unclear. Discussion: The evidence base on BI interventions for patients with AN is scarce. It is not possible to identify types of BI intervention that can be seen as the most promising. Advantages of new technologies such as virtual reality or a combination of BI interventions with techniques for stress reduction are discussed.